The economics of sustainable forest management and wildlife conservation in tropical forests - Byron, R.N. (Columbia University, 2001)
The chapter examines the opportunities and limitations of economics to contribute to sustainable forest management and wildlife conservation. It began with a brief interview of the constraints facing natural resource economists, ending with a discussion of where these individuals can contribute to the sustainable forest management debate. This is followed by a discussion of current efforts to bring about change in the timber harvest status quo. Two case studies reviewing the costs and benefits associated with conventional and reduced impact logging practices are presented. The chapter closes with a discussion of how economics can contribute to the advancement of sustainable forest management practices in the near- and long-term.